Laporan Kasus: Primigravida Sebagai Faktor Risiko Preeklampsia - Istiqomah, Dinni; M, Faisal Abdul Aziz; Sari, Poppy Monika; Siregar, Wanda Feranti; Zulfadli, Zulfadli (CV. Jasa Sukses Abadi, 2024)
Hypertension in pregnancy (HDK) is one of the main causes of maternal death and is a significant cause of maternal and child morbidity. Preeclampsia is the presence of specific hypertension caused by pregnancy accompanied by disorders of other organ systems at a gestational age of more than 20 weeks. There are several risk factors for preeclampsia, namely nullipara (primigravida), age ≥ 40 years, BMI ≥ 35, family history of preeclampsia, multifetal pregnancy and pregnancy interval > 10 years. This study is a case report. Data was obtained from a 22 year old woman who came with complaints of being at term pregnant with complaints of heartburn accompanied by headaches, shortness of breath, nausea and vomiting since 3 weeks before hospital admission. The patient has suffered from hypertension since 7 months of pregnancy, but the patient does not regularly take medication. On physical examination, blood pressure was found to be 152/112 mmHg and urinalysis examination showed positive nitrite, protein 500 mg/dl. The patient was diagnosed with severe preeclampsia. Primigravida is the most important risk factor found in these patients. Several previous studies have shown that there is a relationship between primigravida and the incidence of preeclampsia, where preeclampsia occurs more often in primigravida than multigravida. There are various theories that explain the process of preeclampsia in primigravida, but no theory is considered absolutely correct to date. Therefore, intervention is needed for early prevention and early management of preeclampsia, especially in primigravida.